Cobalt-doped tungsten suboxides for supercapacitor applications - Thalji, Mohammad R.; Ali, Gomaa A. M.; Shima, Jae Jin; Chong, Kwok Feng (Elsevier, 2023)
A crucial hurdle in developing supercapacitors is the creation of metal oxides with nanoscale structures that possess improved chemically active surfaces, ion/charge transport kinetics, and minimized ion-diffusion pathways. A metal-doping strategy to produce oxygen vacancies and increase electrical conductivity has proven effective for designing high-performance materials for energy storage devices. Herein, cobalt-doped tungsten suboxide (Co-doped W18O49) is grown on carbon cloth (CC) using a solvothermal approach and used as an electrode material for supercapacitor applications for the first time. Through this strategy, structurally distorted W18O49 is obtained by detecting a more apparent amorphous area caused by forming more oxygen vacancies with the bending of the lattice fringes. Benefiting from the synergy of more oxygen vacancies, increased lattice spacing, a high specific surface area, and accelerated ion diffusion, the Co-doped W18O49/CC electrode achieves a specific capacity of 475 C g−1 (792 F g−1) at a current density of 1.0 A g−1, which is superior to that of the undoped W18O49/CC (259 C g−1, 432 F g−1) and among the highest reported to date. Interestingly, the asymmetric supercapacitor device assembled using Co-doped W18O49/CC//AC/CC can provide a high energy density of 35.0 Wh kg−1. This strategy proves that the distortion of the W18O49 structure by Co doping improves the ion storage performance and self-discharge behavior. Also, it can enhance the energy storage performance of other electrode materials.